Experimental validation of off‐board EV charging station with reduced active switch count. (14th July 2022) - Khalid, Mohd Rizwan; Asghar, M. S. Jamil; Alam, Mohammad Saad; Hameed, Salman; Khan, Irfan A.
Summary: This paper presents the experimental validation of the proposed off‐board electric vehicle (EV) charging station that complies with the IEEE 519‐2014 power quality (PQ) standard. The proposed EV charging station constitutes a two‐stage power conversion, ac‐dc conversion at the front‐end (interfacing the grid and dc‐link), and dc‐dc conversion at the end‐stage (interfacing dc‐link and EV battery). The ac‐dc conversion stage at the front‐end of the proposed EV charging station with a fewer active switch count makes it unique from other available EV charging. It utilizes multi‐phase transformers to reduce the total harmonic distortion (THD) in the line current drawn, and to improve the power factor (PF). The multi‐phase transformers convert the grid power supply to a multi‐phase supply that makes the input line current stepped and reduces the THD, thus facilitating the reduction of active front‐end power conversion, filter circuitry, and PF correctors. The multi‐phase power supply is rectified to feed the dc‐link from which the EV battery is charged with a dc‐dc converter in constant current (CC) and constant voltage (CV) mode. The experimental validation was performed in a laboratory on a developed prototype of the proposed EV charger. The THD measured in the input line current was 3.78% with high PF (about unity) that meets the recommended IEEE 519‐2014 PQ standard. The efficiency of the charger recorded was 90.4%. A comparative analysis of the proposed EV charge is presented on five metrics namely: PQ, cost, power density, control complexity, and robustness, which confirms the effectiveness of the proposed EV charger. Abstract : Configurations of dc‐fast chargers with common ac‐bus.